Artists emerging : sustaining expression through drawing / Sheila Paine. - Paine, Sheila (Ashgate, 2000)
This text follows seven artists as they find ways to sustain and develop their drawing skill and expressive potential. This study reveals the sequences of their progress and their eventual achievement.